PEMBERDAYAAN PKK DALAM PENGENALAN TOGA SEBAGAI UPAYA PENINGKATAN IMUNITAS DI ERA PANDEMI COVID-19 - Ni Kadek Yuni Lestari; Ni Made Nopita Wati; Desak Made Ari Dwi Jayanti; Ni Luh Putu Thrisna Dewi; I Nyoman Sudarma (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
The global COVID-19 pandemic has been going on for more than a year but has not shown a decrease in cases, even similar cases have emerged caused by the mutated corona virus. The government is trying to socialize the behavior of a healthy lifestyle and the use of TOGA plants to increase body immunity. This service activity aims to increase the knowledge of PKK mothers in using TOGA as a traditional ingredient to increase body immunity. The service method consists of measuring the level of knowledge of PKK mothers by distributing questionnaires, providing education through bold counseling about Covid-19, offering toga plants and herbal herbs. The results of community service activities obtained the main data of respondents aged 36-45 years as many as 45 people (34.4%), most of them with undergraduate education as many as 36 people (27.5%), and working as employees as many as 62 people (47.3%). Before being given counseling the level of knowledge was in the less category 63 people (48.1%) and after being given counseling mostly in the good category as many as 75 people (57.3%), PKK mothers had been given TOGA plants that could be used for making traditional ingredients. This program is expected to be carried out in a sustainable manner to increase public knowledge in increasing immunity during a pandemic and preventing and reducing the transmission of Covid-19 disease in the community.